2011
DOI: 10.1016/j.anbehav.2011.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Social learning of a novel foraging task by big brown bats, Eptesicus fuscus

Abstract: Acquiring information via observation of others can be an efficient way to respond to changing situations or learn skills, particularly for inexperienced individuals. Many bat species are gregarious, yet few studies have investigated their capacity for learning from conspecifics. We tested whether big brown bats (Eptesicus fuscus) can learn a novel foraging task by interacting with knowledgeable conspecifics. In experimental trials 11 naïve bats (7 juveniles, 4 adults) interacted freely with trained bats that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
(42 reference statements)
0
30
0
Order By: Relevance
“…Female Bechstein's bats and greater horseshoe bats (Rhinolophus ferrumequinum (Schreber, 1774)) inherit their foraging areas from their mothers (Kerth et al 2001;Rossiter et al 2002). Wright et al (2011) found that the acquisition of a novel foraging task (catching a tethered mealworm) in the big brown bat (Eptesicus fuscus (Palisot de Beauvois, 1796)) is strongly enhanced by interaction with an experienced conspecific compared with individual trial and error learning. In evening bats (Nycticeius humeralis (Rafinesque, 1818)), naïve individuals follow experienced conspecifics to new food resources from the roost (Wilkinson 1992).…”
Section: Discussionmentioning
confidence: 98%
“…Female Bechstein's bats and greater horseshoe bats (Rhinolophus ferrumequinum (Schreber, 1774)) inherit their foraging areas from their mothers (Kerth et al 2001;Rossiter et al 2002). Wright et al (2011) found that the acquisition of a novel foraging task (catching a tethered mealworm) in the big brown bat (Eptesicus fuscus (Palisot de Beauvois, 1796)) is strongly enhanced by interaction with an experienced conspecific compared with individual trial and error learning. In evening bats (Nycticeius humeralis (Rafinesque, 1818)), naïve individuals follow experienced conspecifics to new food resources from the roost (Wilkinson 1992).…”
Section: Discussionmentioning
confidence: 98%
“…The availability of foraging information has been proposed as an advantage leading to the evolution of bat coloniality [19], and a number of studies have demonstrated social learning in bats [20][21][22][23]. The fringe-lipped bat, Trachops cirrhosus, is a Neotropical carnivore that hunts frog and insect prey by eavesdropping on the prey's mating calls [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Echolocation signals are not directed at an external receiver per se; nevertheless, they can be used as an information source by eavesdroppers [10 -12]. Echolocation calls indicate both the presence and the feeding activity of bats; therefore, they can inform other bats in hearing distance about good hunting grounds [13,14], new foraging tasks [15] or roost sites [16]. A growing body of evidence indicates that social information about the calling bat can be encoded in echolocation calls as well (reviewed in [11,17]).…”
Section: Introductionmentioning
confidence: 99%